2016
DOI: 10.12659/msm.897179
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Protocadherin10 (PCDH10) Methylation in Serum of Prostate Cancer Patients

Abstract: BackgroundProstate cancer is a heterogeneous malignancy with outcome difficult to predict. Currently, there is an urgent need to identify novel biomarkers that can accurately predict patient outcome and improve the treatment strategy. The aim of this study was to investigate the methylation status of PCDH10 in serum of prostate cancer patients and its potential relevance to clinicopathological features and prognosis.Material/MethodsThe methylation status of PCDH10 in serum of 171 primary prostate cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Third, the data were obtained from patients treated at a single center in China, which limits the generalizability of the results to the wider population. Finally, of course, the present study only examined factors that are routinely assessed in the clinical management of PCa, but novel markers such as aberrant DNA methylation [ 40 , 41 ], miRNA expression [ 42 ], and genes involved in inflammation [ 43 ] are promising and should be examined in future studies. Multicenter prospective studies including larger sample sizes are required to confirm the conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the data were obtained from patients treated at a single center in China, which limits the generalizability of the results to the wider population. Finally, of course, the present study only examined factors that are routinely assessed in the clinical management of PCa, but novel markers such as aberrant DNA methylation [ 40 , 41 ], miRNA expression [ 42 ], and genes involved in inflammation [ 43 ] are promising and should be examined in future studies. Multicenter prospective studies including larger sample sizes are required to confirm the conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…One group of proteins whose altered expression has been associated with tumor invasiveness, metastatic dissemination, and poor patient prognosis is the cadherins superfamily. Cadherins are a large multigene family of transmembrane glycoproteins with a crucial role in homophilic cell-cell adhesion, cell polarity, cell proliferation, migration, and differentiation [17,18]. E-Cadherin has been considered the paradigmatic classical cadherin and is mainly expressed in epithelial tissues.…”
Section: Metodologiamentioning
confidence: 99%
“…Sunami et al reported that GSTP1 me , RASSF1A me and RARβ2 me associated with Gleason score and serum PSA levels, whereas GSTP1 me and RARβ2 me also associated with advanced stages of disease [173]. Moreover, individually, serum PCDH17 me , PCDC10 me and PCDH8 me were also associated with advanced clinical stage, higher preoperative serum PSA, as well as lymph node metastasis and shorter biochemical recurrence-free survival [193][194][195]. Besides being also associated with Gleason score, advanced tumor stage and high PSA, CDH13 me was further associated with shorter OS [183].…”
Section: Prognosis Predicition and Monitoringmentioning
confidence: 99%